2020
DOI: 10.3390/nu12020584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beetroot Juice Ingestion on Physical Performance in Highly Competitive Tennis Players

Abstract: Beetroot juice (BJ) contains high levels of inorganic nitrate (NO3−) and its intake has good evidence in increasing blood nitrate/nitrite concentrations. The ingestion of BJ has been associated with improvements in physical performance of endurance sports, however the literature in intermittent sports is scarce. The aim of this study was to investigate whether BJ could improve physical performance in tennis players. Thirteen well-trained tennis players (25.4 ± 5.1 years) participated in the study during their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 51 publications
(78 reference statements)
5
57
0
Order By: Relevance
“…In intermittent sports such as tennis, beetroot juice containing 6.4 mmol nitrate did not show any improvements in either explosive movements (serve velocity, jump, sprint, handgrip force) or perceptual exertion in high-level tennis players [36] with a low risk of bias. These results are similar to the ones found in recent studies in which short and high-intensity movements (such as countermovement jump, isometric strength, or muscular movement concentric velocity) were evaluated after the consumption of beetroot juice containing 6.4-17.7 mmol nitrate [57][58][59].…”
Section: Effects Of Nitric Oxide (No) Precursors In Racquet Sportsmentioning
confidence: 75%
See 4 more Smart Citations
“…In intermittent sports such as tennis, beetroot juice containing 6.4 mmol nitrate did not show any improvements in either explosive movements (serve velocity, jump, sprint, handgrip force) or perceptual exertion in high-level tennis players [36] with a low risk of bias. These results are similar to the ones found in recent studies in which short and high-intensity movements (such as countermovement jump, isometric strength, or muscular movement concentric velocity) were evaluated after the consumption of beetroot juice containing 6.4-17.7 mmol nitrate [57][58][59].…”
Section: Effects Of Nitric Oxide (No) Precursors In Racquet Sportsmentioning
confidence: 75%
“…Most of the trials assessed showed an unclear level in the criteria of selection bias, both in the randomized treatment order and in the evaluation of the carry-over effect. Only the trials by Vergauwen; 1998, [ 26 ] Lopez-Samanes; 2020 [ 36 ] and Abian; 2015 [ 40 ] suitably described the tools used for randomization treatment, while trials by Wu; 2010 [ 34 ], Yang; 2017 [ 38 ], Abian; 2015 [ 40 ] and Muller; 2019 [ 45 ] used tests to check if the washout time between conditions was suitable. Moreover, most of the studies also showed a high risk of detection bias except for trials by Gallo-Salazar; 2015 [ 30 ] and Abian; 2015 [ 40 ], which specifically indicated that blinding was kept until the statistical analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations